A highly tunable microwave oscillator based on MTJ STO technology. Issue 9 (September 2014) - Chen, T.; Dürrenfeld, P.; Rodriguez, S.; Åkerman, J.; Rusu, A.
ABSTRACT This article presents a fully ESD‐protected, highly tunable microwave oscillator based on magnetic tunnel junction (MTJ) spin torque oscillator (STO) technology. The oscillator consists of a compact MTJ STO and a 65 nm CMOS wideband amplifier, which amplifies the RF signal of the MTJ STO to a level that can be used to drive a PLL. The (MTJ STO + amplifier IC) pair shows a measured quality factor (Q) of 170 and a wide tunability range from 3 to 7 GHz, which demonstrate its potential to be used as a microwave oscillator in multiband, multistandard radios. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:2092–2095, 2014